On Fluid and Thermal Dynamics in a Heterogeneous CO2 Plume Geothermal Reservoir - Tianfu Xu; Huixing Zhu; Guanhong Feng; Yilong Yuan; Hailong Tian (Geofluids)
CO2 is now considered as a novel heat transmission fluid to extract geothermal energy. It can achieve both the energy exploitation and CO2 geological sequestration. The migration pathway and the process of fluid flow within the reservoirs affect significantly a CO2 plume geothermal (CPG) system. In this study, we built three-dimensional wellbore-reservoir coupled models using geological and geothermal conditions of Qingshankou Formation in Songliao Basin, China. The performance of the CPG system is evaluated in terms of the temperature, CO2 plume distribution, flow rate of production fluid, heat extraction rate, and storage of CO2. For obtaining a deeper understanding of CO2-geothermal system under realistic conditions, heterogeneity of reservoir’s hydrological properties (in terms of permeability and porosity) is taken into account. Due to the fortissimo mobility of CO2, as long as a highly permeable zone exists between the two wells, it is more likely to flow through the highly permeable zone to reach the production well, even though the flow path is longer. The preferential flow shortens circulation time and reduces heat-exchange area, probably leading to early thermal breakthrough, which makes the production fluid temperature decrease rapidly. The analyses of flow dynamics of CO2-water fluid and heat may be useful for future design of a CO2-based geothermal development system.